Scholarly Podcasting for Research Dissemination: A Scoping Review - Lindsay Persohn; Stephanie Branson (SAGE Open)
The purpose of this scoping review is to understand ways in which podcasting is used to communicate research findings and mobilize knowledge to a public audience. We address the use of podcasting as a broad research dissemination tool, as opposed to podcasting as a tool in formal education contexts. We summarize findings of individual studies, then identify themes across those studies. We offer definitions of specialized terms, as well as affordances and constraints of scholarly podcasting. We found scholarly podcasting allows a way for researchers to share research knowledge with the public, mobilizing knowledge more readily to a broader audience. We draw parallels to and outline departures from traditional publishing. We offer directions for future research, noting that podcasting holds the potential to impact public understanding of research by moving beyond the traditional forms of knowledge dissemination to cultivate a more equitable future for research.